Identification of oocyte reprogramming factors and mechanisms - Mola, Choulia (2017)
The ability of the oocyte to reprogram paternal chromatin is widely accepted. The oocyte cytoplasm has been reported to contain activities that alter the histone composition, demethylate and unwind highly methylated paternal DNA upon fertilization and lead to zygote formation. The same events are mimicked during the course of cell reprogramming, where somatic cells exposed to the oocyte environment acquire a pluripotent character. Amphibian oocytes have been widely used to study the reprogramming attributes of the female germ cells for over half a century. The size of amphibian oocytes renders them good candidates for technical manipulations, as well as protein biochemistry studies. Oocytes harvested from the amphibian axolotl were utilised in the present study to delineate the oocyte reprogramming machinery. Previous studies have reported the presence of key pluripotency factor orthologs, such as Nanog, in the axolotl oocyte, thus rendering it an interesting tool for the study of the chromatin remodelling and pluripotency networks as well as their interplay. To study these networks, identification of the physical interactors of the Nanog protein or the Nanog promoter was attempted. One of the key events taking place during cell and paternal chromatin reprogramming is demethylation. The removal of the methyl mark that is deposited over genetic loci during cell differentiation is linked with the transcriptional activation of the respective loci. Demethylation is therefore fundamental for the activation of pluripotency-associated factors both in fertilisation and cell reprogramming. The leading theory behind demethylation is the successive oxidation of the methyl mark to formyl and carboxyl and its subsequent removal from Thymine DNA Glycosylase (TDG). Ten Eleven Translocation (TET) family proteins catalyse methyl oxidation and therefore utilise demethylation. Additional demethylation pathways have also been supported by findings, specifically in the context of the oocyte. Base Excision Repair (BER) and Nucleotide Excision Repair (NER) factors have been associated with DNA demethylation occurring immediately after fertilisation. It is therefore fundamental to delineate the demethylation mechanism facilitated by the oocyte in the early stages of development. The identification of oocyte demethylation factors and mechanisms will greatly improve our understanding of demethylation as well as improve current cell reprogramming methodologies by using the more efficient oocyte demethylation mechanism. To delineate the demethylation mechanism employed by the oocyte and contribute to the debate of TET oxidation versus NER or BER demethylation via DNA repair in the context of the oocyte, oocyte factors preferentially binding to different cytosine modifications were analysed. The murine Nanog promoter, a genetic locus activated during cell reprogramming, harboured the different cytosine modifications in an attempt to see how each one would affect its transcriptional status. As a result, TET factors were not discovered to bind any of the cytosine modifications while both NER and BER pathway proteins were found to be significantly enriched in the case of methylcytosine. The results obtained therefore support previous findings and advocate for a TET independent DNA demethylation occurring through DNA repair. While teams researching demethylation through DNA repair have supported either NER or BER, the findings unveiled in this thesis advocate for the two pathways acting in concert in the recognition and potential removal of DNA methylation. It also has to be noted that it is the first time an experiment of this kind is carried out in the context of the oocyte and the findings offer a unique insight into oocyte demethylation dynamics. Taking into account the data obtained and previous research, a new DNA demethylation model is proposed. The model advocates for NER taking the lead in DNA demethylation, creating patchy demethylated sites that are subsequently recognised and demethylated via the BER pathway.